The impacted oro-pharnygeal fish bone-surgeon’s dilemma - Munjal, Manish; Puri, Sandeep; Munjal, Shubham; Puri, Aneesha; Grewal, Harpreet; Talwar, Shivam; Chawla, Deeksha; Kaur, Hardeep; Sandhu, Lovleen; Pillai, Anjana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Pisces are a delicacy on the table of almost every non-vegetarian household. Unfortunately, pharyngeal impaction of fish bones is a frequent emergency in the oto-rhino-laryngological clinics or trauma units of tertiary health care facilities. Sequentially the sites of retention noted are the lymphoid tissue of tonsillar fauces, the coffin corner, the base of the tongue, either valleculae and the pyriform sinuses. Lancinating pain on deglutition with a typical history is diagnostic, therapy necessitating timely intervention to avoid an untoward sequel. It poses a queer situation for the laryngologist whether to go ahead and straightaway attempt to extract the same under local anesthesia or wait for the requisite 6 hrs for administration of general anesthesia. The waiting duration being equally painful and a testing period for the patient and the surgeon alike. The latter is more apprehensive about deeper migration of the bone. The out-patient extraction in a cooperative individual was undertaken with a three-handed modality, adopting an angled viewing telescope and respective instrumentation.